AB1465-HPR The cost of hospitalisation for knee osteoarthritis in france in 2010. (23rd January 2014) - Rannou, F.; Bertin, P.; Grange, L.; Taieb, C.
Abstract : Background: The cost of an osteoarthritic patient has not been estimated for several years Objectives: Evaluate the cost of hospitalization of knee osteoarthritis patients in France in 2010 Methods: For hospital stays (medical, surgery and obstetrics)and for patients treated under Follow-up care and Rehabilitation (formerly "halfway house"), use of the PMSI data.The evaluation we carried out is based on the last 2 years of available data - 2009 and 2010 Results: In France, around 85 000 patients are treated yearly in hospital for knee osteoarthritis. They are made up of 62% women and 38% men, with an average age of 70. The average hospital stay was 9 days (9.1 average per patient per year). The average annual cost of hospital treatment for one patient is estimated at around €7700 61% of patients are then treated with rehabilitation, of which 67% are women. The average age of patients treated with rehabilitation is 71. Each patient stayed for an average of 35 days, either full or partial hospitalization with functional reeducation or medical follow-up treatment. The annual treatment cost of a patient in rehabilitation is estimated at €6986. In total, the average annual cost for all patients treated in hospital (medical/surgery/obstetrics + rehabilitation) for knee osteoarthritis in 2010 is estimated at €11961. In total, the overall annual cost of one patient treated in hospital (medical/surgery/obstetrics + rehabilitation) for knee osteoarthritis in 2010 is estimated at €1322 million euros. Conclusions: The last study evaluating the cost of osteoarthritis in France reported 127 000 short-stay admissions, 175 000 follow-up and/or rehabilitation treatment days, and 118 000 knee or hip replacements, the overall cost of hospitalizations is therefore 820 million euros in 2002. Our evaluation demonstrates that this cost evaluation is outdated, as the amount is lower than the overall cost of hospitalizations linked to osteoarthritis of the knee. References: COART - Le Pen and coll, Revue du rhumatisme, December 2005 Disclosure of Interest: F. Rannou: None Declared, P. Bertin: None Declared, L. Grange: None Declared, C. Taieb Employee of: PFSA